Nonuniform Deformation Instability Mechanism of Gob-Side Entry Retained in Inclined Coal Seam and Stability Control - Xubo Qiang; Ji Li; Chaosen Chen; Jihui Dong; Yingjian Zheng; Zhong Chen (Applied Sciences, 2023)
In this study, the nonuniform deformation and failure of the goaf retaining roadway in an inclined coal seam due to repeated mining have been investigated by field verification, theoretical analysis and numerical simulation. As a case study, 3131 headentry of a coal mine in Sichuan province was considered. The deformation characteristics of the surrounding rock along the gob of inclined coal seam and the distribution characteristics and evolution of the plastic zone and stress field direction of gob-side entry retaining (GER) in 3131 coal faces during the service period were also studied. Based on the mechanical model of the plastic zone of surrounding rock, the stress field direction effect of nonuniform expansion of the plastic zone is explained, and the nonuniform deformation damage mechanism of the inclined coal seam along the empty tunnel is revealed. The results show that the plastic zone of the side always expands along the coal seam towards the side affected by mining during the whole service period of GER in the inclined coal seam, and the plastic zone of the roof and floor expands to the deep surrounding rock; and the expansion degree of the soft coal (rock) seam position of the roadway is the highest. At the same time, the direction of the surrounding rock stress field will be deflected during the service period of GER, and the plastic zone expands unevenly under the action of the coal seam dip angle and stress direction. The nonuniform expansion degree of the plastic zone is the largest when the angle between the maximum principal stress and the coal (rock) layer is 45° (±5°). A collaborative support method with “supporting and reducing span” as the core in GER is also proposed in this work. Field tests were also carried out. During the retaining period, the displacement of the roof and floor was reduced from 250 mm to 125 mm.